Antenna synthesis based on the ant colony optimization algorithm - Slyusar, V. I.; Ermolaev, S. Y. (Видавництво Національного університету "Львівська політехніка", 2009)
This report are described the versions and the synthesis results of new designs of electrically small antenna based on ant colony optimization algorithms. To study the parameters of the frame and non-loopback vibrators MMANA package was used. Geometric forms that were obtained might be used as contour lines of printed, slot antenna or as forming surface of the crystal dielectric resonator antenna. A constructive meta-heuristic search algorithm for optimization of the antennas forms using solutions of travelling salesman problem (TSP).
Keywords: ant colony system (ACS); travelling salesman problem (TSP); MMANA